Comparative study of product innovation systems. (1st January 2003) - Ichimura, Takaya; Ishii, Kazuyoshi; Tuominen, Markku; Piippo, Petteri
Product innovation management, which includes new product development and product improvement, is one of the most important managerial concerns. The establishment of an effective and flexible product innovation system is necessary in every company in order to achieve competitive advantage, but the focal point and process of product development differ with regard to managerial strategy and surrounding conditions. The purpose of this study is to clarify the fundamental activity of product innovation processes and to identify the elemental functions of product development, thus comparing the pattern of development in practical investigations. In order to achieve this goal, we take the common functions of product innovation by extracting them from practical case studies. As a result we compare the cases and discuss the characteristics of a product innovation system.